Initiating sacubitril/valsartan (LCZ696) in heart failure: results of TITRATION, a double‐blind, randomized comparison of two uptitration regimens. (12th May 2016) - Senni, Michele; McMurray, John J.V.; Wachter, Rolf; McIntyre, Hugh F.; Reyes, Antonio; Majercak, Ivan; Andreka, Peter; Shehova‐Yankova, Nina; Anand, Inder; Yilmaz, Mehmet B.; Gogia, Harinder; Martinez‐Selles, Manuel; et al.
Abstract: Aims: To assess the tolerability of initiating/uptitrating sacubitril/valsartan (LCZ696) from 50 to 200 mg twice daily (target dose) over 3 and 6 weeks in heart failure (HF) patients (ejection fraction ≤35%). Methods and results: A 5‐day open‐label run‐in (sacubitril/valsartan 50 mg twice daily) preceded an 11‐week, double‐blind, randomization period [100 mg twice daily for 2 weeks followed by 200 mg twice daily ('condensed' regimen) vs. 50 mg twice daily for 2 weeks, 100 mg twice daily for 3 weeks, followed by 200 mg twice daily ('conservative' regimen)]. Patients were stratified by pre‐study dose of angiotensin‐converting enzyme inhibitor/angiotensin‐receptor blocker (ACEI/ARB; low‐dose stratum included ACEI/ARB‐naïve patients). Of 540 patients entering run‐in, 498 (92%) were randomized and 429 (86.1% of randomized) completed the study. Pre‐defined tolerability criteria were hypotension, renal dysfunction and hyperkalaemia; and adjudicated angioedema, which occurred in ('condensed' vs. 'conservative') 9.7% vs. 8.4% ( P = 0.570), 7.3% vs. 7.6% ( P = 0.990), 7.7% vs. 4.4% ( P = 0.114), and 0.0% vs. 0.8% of patients, respectively. Corresponding proportions for pre‐defined systolic blood pressure <95 mmHg, serum potassium >5.5 mmol/L, and serum creatinine >3.0 mg/dL were 8.9% vs. 5.2% ( P = 0.102), 7.3% vs. 4.0% ( P = 0.097), and 0.4% vs. 0%, respectively. In total, 378 (76%) patients achieved and maintained sacubitril/valsartan 200 mg twice daily without dose interruption/down‐titration over 12 weeks (77.8% vs. 84.3% for 'condensed' vs. 'conservative'; P = 0.078). Rates by ACEI/ARB pre‐study dose stratification were 82.6% vs. 83.8% ( P = 0.783) for high‐dose/'condensed' vs. high‐dose/'conservative' and 84.9% vs. 73.6% ( P = 0.030) for low‐dose/'conservative' vs. low‐dose/'condensed'. Conclusions: Initiation/uptitration of sacubitril/valsartan from 50 to 200 mg twice daily over 3 or 6 weeks had a tolerability profile in line with other HF treatments. More gradual initiation/uptitration maximized attainment of target dose in the low‐dose ACEI/ARB group.